2002
DOI: 10.1163/22941932-90000297
|View full text |Cite
|
Sign up to set email alerts
|

Within-Tree Variation in Growth Rate and Cell Dimensions in the Wood of Black Locust (Robinia Pseudoacacia)

Abstract: Black locust (Robinia pseudoacacia L.) is regarded as an important natural resource almost throughout the world but relatively little is known about the within-tree variability of the anatomical characteristics of its wood. Discs 2 cm thick were cut at 2.25 m intervals, from the ground level to the top from ten black locust trees, 18–37-years-old, from the University Forest of Taxiarchi, Chalkidiki, Greece. The discs were used for the determination of growth rate and cell dimensions (fiber length and vessel me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 5 publications
5
10
0
1
Order By: Relevance
“…1 and 2, Table 1). As in previous studies (Ismail et al 1995;Lei et al 1996;Gartner et al 1997;Helinska-Raczkowska and Fabisiak 1999;Woodcock et al 2000;Adamopoulos and Voulgaridis 2002;Leal et al 2003), the vessel size increased radially away from the pith in the trunk sections, though in the lower trunk, the increase from the intermediate to the outer wood was not significant. Because the increase in vessel size in the trunk was greater than the initial decrease in frequency, there was an increase in the vessel area fraction from the core wood to outer wood in the trunk sections.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…1 and 2, Table 1). As in previous studies (Ismail et al 1995;Lei et al 1996;Gartner et al 1997;Helinska-Raczkowska and Fabisiak 1999;Woodcock et al 2000;Adamopoulos and Voulgaridis 2002;Leal et al 2003), the vessel size increased radially away from the pith in the trunk sections, though in the lower trunk, the increase from the intermediate to the outer wood was not significant. Because the increase in vessel size in the trunk was greater than the initial decrease in frequency, there was an increase in the vessel area fraction from the core wood to outer wood in the trunk sections.…”
Section: Resultssupporting
confidence: 81%
“…It has frequently been observed that the radius and length of vessels and tracheids increases during the first years of the growth of a tree, both in angiosperms (Ismail et al 1995;Lei et al 1996;Gartner et al 1997;Helinska-Raczkowska and Fabisiak 1999;Adamopoulos and Voulgaridis 2002;Leal et al 2003) and in gymnosperms (Gartner 1995;Mencuccini et al 1997;Spicer and Gartner 2001). The wood produced during these first years when the cambium changes rapidly is known as juvenile wood.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile xylem typically has shorter wood fibers and larger microfibril angles relative to the cell axis than those of mature xylem (Bonham and Barnett 2001;Adamopoulos and Voulgaridis 2002;Honjo et al 2005), resulting in a lower mechanical strength. In resprouts, the shoot age was 1 year old, whereas adult stems of similar size were several years old.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have also been rare in other countries, and it is difficult to compare them with our research due to differences in climate and location (Klašnja et al, 2000;Adamopoulos & Voulgaridis 2002;Motta et al, 2009;Adamopoulos et al, 2010). The statistical indicators determined in our research (x, x w, min, max, sd, V), describing the site chronology of the black locust in Wroclaw, differed significantly from indicators for other site chronologies of deciduous trees in this part of Europe (Klašnja et al, 2000;Feliksik et al, 2007;Jansons et al, 2015).…”
Section: Discussionmentioning
confidence: 76%